Natureza irreal ou fantástica realidade?: uma reflexão sobre a melancolia religiosa e suas expressões simbólicas na obra de Hieronymus Bosch - Ioshimoto, Lilian Wurzba (2009)
This research deals with religious melancholy and its symbolical expressions in the Hieronymus Bosch s pictorial work. Starting from Robert Burton s definition, it investigates the appropriateness of the concept of religious melancholy as a description of the paradox of human condition. Going all the way from the first definitions of the phenomenon, in the Hippocratic corpus or in philosophy, through its presence in medieval theology, until reaching as far as modern psychiatry, it claims, based on the categories of Carl Gustav Jung analytical psychology, that it can be best understood as a symbol expressing the soul s most typical process, a psychic state representative of the duality of human existence, rather than as mere pathology. Severed from its original ontological state of identify to become something a being in time and space, the soul must recognize itself as fragment of what is real rather than as an unreal whole; it must accept that it is a creature, not the creator. This process, going as it were beyond rational grasp (since it is representative of the relation of the I with the depths of the psyche), can only translate into images, from the sublime and incomprehensible to the perverse and grotesque. Fantastic images like the ones found in the figurative universe of Bosch s work, which, apart from its open satirical and pedagogical purpose, displays not the fear of death or man s lack of foundation, but the on-going tension between the I, the world and God the angst of living. The present work is, thus, a symbolic analysis of Hieronymus Bosch based on the many commentators of his ground-breaking body of work, on the theoretical views on melancholy developed throughought history and Jungian concepts, with the purpose of identifying religious melancholy in Bosch s labyrinthic landscapes as an essential feature of the human condition